Future-ready accountant: Upskilling and life-long learning in the age of digital transformation - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 2021)
Upskilling and life-long learning are two key phrases that Education Minister Lawrence Wong highlighted in his speech at the Straits Times Education Forum 2021. The rapid emergence of digital technologies has disrupted many industries, including accountancy sector. While accounting jobs will continue to exist and grow, the way that accounting work is carried out is no longer the same. Accounting functions are increasingly relying on digital technologies to enable their work. For instance, data analytics is deployed in audit and forensics to detect irregular patterns in accounting transaction. Machine learning algorithms are used to sharpen forecasting models to predict sales trends. Such digital evolution in the accountancy sector has witnessed a growing call for ‘digital accountant’: Accountants that are equipped with relevant digital knowledge and skillsets that allow them to handle and manipulate large quantum of data in daily accounting tasks and develop deep analysis in supporting business decision-making.